E-251 Endovascular treatment of cerebral vascular lesions using nickel/nitinol containing devices in patients with nickel allergies. (23rd July 2022) - Baranoski, J; Catapano, J; Rutledge, C; Cole, T; Winkler, E; Srinivasan, V; Jadhav, A; Ducruet, A; Albuquerque, F
Abstract : A nickel hypersensitivity is the most common metal allergy with an estimated prevalence of 10–15%. Nickel is found in many of the new endovascular treatment devices, including flow-diverting stents, self-expanding stents, and intrasaccular occlusion devices. With the increased usage of these devices, the relative risk when they are used in patients with nickel and other metal allergies remains to be fully elucidated. We sought to review the outcomes of patients with documented nickel/metal allergies who underwent endovascular cerebral pathology treatment with nickel-containing devices. We performed a retrospective analysis of our endovascular database and identified patients with a documented nickel and/or metal allergies who underwent treatment with a nickel-containing device from 7/2018 through 3/2021. Clinical, radiological, and outcome data were analyzed. Seven patients (100% female) with documented nickel (4) or other metal (3) allergies with 9 cerebrovascular lesions underwent treatment using a total of 9 nickel containing devices (7 flow-diverting and 2 self-expanding stents). No peri-procedural complications including any apparent allergic reactions, thromboembolic events, or in-stent stenoses occurred. None of these patients received peri-procedural treatment with steroids or antihistamines. Clinical follow-up is available for all patients (mean=18.5months, range=5–37.5months) with no evidence of procedurally-related neurological symptoms or symptoms attributable to nickel/metal allergic reactions. Angiographic follow-up is available for 6 of the 7 patients (mean=6months; range=0.5–14.5months). In 5 of these 6 patients, complete obliteration of their 7 vascular lesions with no evidence of in-stent stenosis or other vessel pathology was achieved. In this case series, the endovascular treatment of cerebrovascular lesions in patients with documented nickel and other metal allergies with a nickel-containing device did not result in any adverse outcomes and was overall safe and effective. Disclosures: J. Baranoski: None. J. Catapano: None. C. Rutledge: None. T. Cole: None. E. Winkler: None. V. Srinivasan: None. A. Jadhav: None. A. Ducruet: 2; C; Medtronic, Stryker, Cerenovus, Penumbra, and Koswire. F. Albuquerque: None.